Konversi Utang PT Menjadi Saham Berdasarkan UU Kepailitan PKPU Nomor 37 Tahun 2004 - Rafi Muhammad Ave; Rembrant; Yasniwati (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
This study aims to analyze the regulation of debt-to-equity conversion in limited liability companies within the framework of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and examine the considerations of commercial court judges in ratifying peace plans through a case study of Commercial Court Decision Number: 497/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst involving PT. Waskita Beton Precast Tbk (WSBP). The research method employs a normative juridical approach with descriptive-analytical characteristics, utilizing secondary data consisting of primary, secondary, and tertiary legal materials collected through document study and library research. Data analysis techniques use qualitative methods through interpretation, conclusion drawing, and presentation in sentence form based on expert opinions and statutory regulations. Research results indicate that debt restructuring through debt-to-equity conversion is not specifically regulated in the Bankruptcy Law, making legal foundations rely solely on technical provisions such as Articles 222, 281 of the Bankruptcy Law, and Article 41 of the Company Law, which potentially conflict with business continuity and balance principles, particularly in the WSBP case that was under special monitoring by the Financial Services Authority yet still obtained homologation ratification that could potentially harm creditors